Assessment of Body Mass Index (BMI) and General Health Status of Male Auto-Rickshaw Drivers in Garia, Kolkata (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: auto-rickshaw driver; Kolkata; body mass index; health status; binomial test; cross-sectional study